A new leadership for a new ecclesiology - I. D. Mothoagae; L. A. Prior (Acta Theologica)
While many berate the poor level of leadership in the Church, it is noticeable that the same complaint is made about leadership in the corporate world. It is the authors’ contention that the new ecclesiology that has been spoken and written about during the past decades cannot be implemented until there is a change in the understanding and practice of Church leadership. Much could be learned from the changes taking place in corporate management. This paper considers a number of leadership models developed over recent years and shows how these could bring renewal to the Christian Church if applied in ecclesial circles.